Representativeness Bias dan Demografi dalam Membuat Keputusan Keuangan - Peter Garlans Sina (Jurnal Manajemen Maranatha, 2014)
Abstract: Financial decision making is always related to the need of information, however in processing information an individu cannot be fully rational because individu often uses the representatives bias. The research was aimed to indicatewhether any tendency experiencing the representative bias and to analysis whether demography factors, includes gender, marital status, and age who those experiencing representative bias. The research sample was the postgraduate students of Satya Wacana Christian University of Salatiga by amount 86 samples.Data were acquired by distributing the questioners. The result of the study showed that majority of respondent have the tendency in experiencing the representative bias, while in demography factors includes gender, marital status, and age category showed that none of the factors experience the representative bias.Keywords: representative bias, gender, marital status, age, financial decision